Estimation of fluoride level in drinking water samples of Raipur District, Chhattisgarh - Anubhuti Jain; Abhinav Parakh; G Y Yunus; N Naveen; Kamlesh Kumar Jain; Ruchi Agrawal (Wolters Kluwer Medknow Publications, 2021)
Background: The fluoride intake in the general population derives chiefly from drinking water and dietary sources. The presence of fluoride in groundwater for drinking purposes may be beneficial or detrimental depending on its concentration and the amount ingested. Objective: The objective of the study was to estimate the concentration of fluoride in drinking water sources of Raipur district. Methodology: A descriptive cross-sectional study was carried out for fluoride mapping of Raipur district. Samples of drinking water were collected from 50 different sites of 20 villages. The concentration of fluoride in drinking water was analyzed using ion-selective electrode method. Results: In all the water samples analyzed, there was the presence of trace amount of fluoride, which ranged from 0.2 ± 1.22 ppm with the mean concentration of 0.411 ± 0.180 ppm. Conclusion: Fluoride levels in groundwater were in trace quantity and well below the optimal level of fluoride necessary for caries prevention.